QUALITY IN MEDICINESelected methods for the statistical analysis of qualitative data exemplified by the New York Heart Association and Canadian Cardiovascular Society classifications - Sobol, Maria; Kwasiborski, Przemysław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
The aim of this paper is to revisit the statistical methods used in the analysis of qualitative data samples. Qualitative data are not measurable. The classifications used in cardiology, such as the Canadian Cardiovascular Society (CCS) classification or the New York Heart Association (NYHA) classes, constitute examples of such data. The CCS classification consists of four subclasses, to which patients are assigned on the basis of the subjective severity of angina pectoris. The NYHA classification consists of four subclasses as well, but uses the degree of physical activity limitation due to heart disease as its criterion. The choice of an appropriate method of statistical analysis depends, above all, on the correct assignment of the analyzed data to one of the two groups: qualitative or quantitative.